Evaluation of the Genotoxicity of Medicinal Plant Extracts for Their Potential Use in Anticancer Phytotherapy - Rogelio Paniagua-Pérez,; Eduardo O. Madrigal-Santillán,; Isela Álvarez-González,; Eduardo Madrigal-Bujaidar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
A systematic review was carried out on the production and publication of research papers related to the study of Genotoxicity, Plant Extracts, Medicinal Plants and Phytotherapy under the PRISMA approach (Preferred Reporting Items for Systematic reviews and Meta-Analyses). The purpose of the analysis proposed in this document was to know the main characteristics of the publications registered in the Scopus and Wos databases during the study of the proposed variables, achieving the identification of 24 publications in total. Thanks to this first identification, it was possible to refine the results through the keywords entered in the search button of both platforms, which were Genotoxicity, Plant Extract, Medicinal Plants, Phytotherapy, reaching a total of 15 documents, excluding duplicates and those that did not meet the analysis criteria. The results will identify patterns, limitations and gaps in current research, providing a solid basis for the development of safe and effective therapies based on natural products. This review highlights the importance of a rigorous approach in the assessment of genetic toxicity to enhance the responsible use of herbal medicine in oncology.